2017
DOI: 10.1002/apj.2124
|View full text |Cite
|
Sign up to set email alerts
|

CuO‐loaded hydrophobically modified chitosan as hybrid carrier for curcumin delivery and anticancer activity

Abstract: The hydrophobic modification of chitosan was performed by the incorporation of aromatic phendione to the amino group of chitosan to improve the hydrophobic drug encapsulation efficiency and anticancer activity. The phendione‐modified chitosan was coated with the copper oxide (CuO) nanoparticles to obtain the hybrid material for the model drug (curcumin) delivery. The synthesized hybrid nanoparticles were characterized by Fourier transform infrared, proton nuclear magnetic resonance, thermogravimetric analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
(58 reference statements)
1
6
0
Order By: Relevance
“…Also, all the studied factors (copper oxide nanoparticles, alginate biopolymer and stirring time) were effective on the anticancer activity of alginate-copper oxide nanocomposite. In agreement with the results obtained, previous studies have also reported the anticancer activity of copper oxide nanoparticles and the nanocomposites containing those [21], [22], [23]. Jeronsia et al ., [22] synthesised the copper oxide nanoparticles using the coprecipitation method and evaluated their anticancer activity at different levels against the MCF-7 cell line.…”
Section: Discussionsupporting
confidence: 90%
“…Also, all the studied factors (copper oxide nanoparticles, alginate biopolymer and stirring time) were effective on the anticancer activity of alginate-copper oxide nanocomposite. In agreement with the results obtained, previous studies have also reported the anticancer activity of copper oxide nanoparticles and the nanocomposites containing those [21], [22], [23]. Jeronsia et al ., [22] synthesised the copper oxide nanoparticles using the coprecipitation method and evaluated their anticancer activity at different levels against the MCF-7 cell line.…”
Section: Discussionsupporting
confidence: 90%
“…FTIR results are given in Figure 3. The peaks located at around 3,663, 3,588, 3,571, 3,384, 3,482, 2,972, and 2,886 cm −1 resembles to O–H stretching vibration, 28 and 1,150, 1,086, 1,071, 987, and 984 cm −1 resembles to asymmetric stretching vibrations of S–O bonds. The peaks at 873, 849, 780, and 748 cm −1 are due to bending vibrations of Cu–OH groups with different hydrogen bonds.…”
Section: Resultsmentioning
confidence: 95%
“…The curcumin release from the hydrogel was increased with increased curcumin loading concentrations because of an increased osmotic potential which leads to the release of more curcumin from the hydrogel into the release medium. 51 Kinetic Models. The curcumin release data from the nanocomposite hydrogel and pure chitosan−cellulose hydrogel obtained were applied to various kinetic models such as zero order, first order, Korsmeyer−Peppas, and Higuchi as shown in Figure S4.…”
Section: ■ Results and Discussionmentioning
confidence: 99%